PERANCANGAN PLTS TERAPUNG UNTUK MENDUKUNG WISATA HIJAU DI BENDUNGAN TAMBLANG, DESA SAWAN, KABUPATEN BULELENG - Yoga Laksana, K. Cakrawenda; Dwi Giriantar, I.A.; Sukerayasa, I W. (Jurnal SPEKTRUM; Vol 10 No 3 (2023): Jurnal SPEKTRUM, 2023)
The Province of Bali have many dams, one of it is the Tamblang Dam, which is located in Sawan Village, Sawan District, Buleleng Regency. The Government of Buleleng Regency is planning to make Tamblang Dam as a new Tourist Destination Area (Daerah Tujuan Wisata or (DTW) in order to improve the existing tourism conditions in North Bali. It is planned to utilizing Renewable Energy (Energi Baru Terbarukan or EBT) sources to support the needs of DTW and to support government programs to reaching the Bali's clean energy target on 2050. The Renewable Energy Power Plant that will be designed is a Floating Solar Photovoltaic (PV) Power Plant, as it the potential source of energy considering that Indonesia is located on the equator. The Solar PV Power Plant is designed using the tool from website by utilizing 5% of the surface area of the dam water which is 4,561.97 m2, based on Kementrian PUPR no 6 Tahun 2020 regulation. So that a Floating Solar PV Power Plant capacity of 0.6 MW is obtained by using 1,533 solar modules and produce energy reaching of 926,539 kWh in a year. The designed Floating PV need an initial investment cost of IDR 13,551,481,157, with the result of economic analysis, obtained value of each parameter including the NPV value is IDR 7,470,053,884, BCR is 2.66, and PP is less than 25 years.